Transformasi Karakter ASN: Strategi Pendidikan Nilai dan Integritas di Era Digital - Jumiati, Jumiati; Pratama, Intan Elfina; Saputra, Boni (CV. ITTC INDONESIA, 2025)
The transformation of the character of the State Civil Apparatus (ASN) is the main foundation in building a clean, responsive, and competitive bureaucracy in the digital era. This article presents an in-depth study of the strategy of educational values ​​and integrity to form the character of ASN that is adaptive to technological developments and the challenges of modern bureaucracy. Using the literature study method and descriptive-qualitative approach, this paper analyzes the concepts of value-based learning, corporate universities, transformative leadership, and ethical digital literacy. The results of the study indicate that the formation of the ideal ASN character must be carried out systematically, through synergy between institutions, instilling a work culture with integrity, and involving the community as supervisors. These findings are expected to be a strategic reference for policy makers and implementers of bureaucratic reform in Indonesia.